The Quest of Self-Directed Learning of Adult EFL Learners In Indonesian Higher Education Context - Dewi, Nita Sari Narulita; Marlina, Neni; Supriyono, Yusup (JEELS (Journal of English Education and Linguistics Studies), 2019)
This research is aimed at questing adult EFL learners’ self-directed learning performance in an Indonesian University. A case study is purposely employed to probing the learning behavior performed by adult learners when English language learning is taken as the context of this research carried out. Three student teachers are determined to be interviewed to obtain data. The acquired data is analyzed using thematic analysis by Braun and Clarke (2006). The study discovers that the EFL learners performed various activities presenting their self-directed learning in terms of learning motivation, learning strategy, selfmonitoring, and social competence. This research contributes to body knowledge of English language learning at higher education in which a teacher will be able to choose or select appropriate teaching strategies dealing with learners’ learning behaviour promoting autonomous learning. The findings also suggest the learners to conduct learning process properly since selfdirected learning enables the learners to maximize their both internal and external potentials in order to achieve better English achievement.